Looking for land allocations for poplar in rural areas considering optimization and protection of natural resources usage - Czarnecki, Adam; Jonczak, Jerzy (Ecological Questions, 2013)
The paper is a case-study of the possibilities for poplar introduction into rural landscape based on the example of Grodziczno commune area. The ultimate outcome of the study are maps, which indicate areas where farmers can consider introduction of poplar cultivation as an adequate response to external conditions, such as prices and demand for food products and regulations, as well as internal conditions - input for production, soil, water, landscape values protection and for overall improving of farm performance in terms of sustainability.